High-stakes assessment in elementary education teacher preparation: Educators' perceptions and actions resulting in curriculum change - Carla Lynn Tanguay (Arizona State University, 2020)
Policy makers have begun requiring teacher performance assessments, such as edTPA®, with established validity and reliability in teacher education for certification, program approval, and/or accreditation (Darling-Hammond Hyler, 2013). Proponents of edTPA argue that the measure is an authentic yet standardized way to assess candidate readiness for teaching and may be beneficial for program renewal and professionalization of the teaching force (Darling-Hammond, 2010; Wei Pecheone, 2010). Others recognize unintended consequences of a single, standardized assessment which may narrow the curriculum (Kornfeld, Grady, Marker, Ruddell, 2007); create tensions for teacher candidates who are learning and developing; (Meuwissen Choppin, 2015); and overlook program values important for preparing candidates to teach in a global society (Sato, 2014). This case study uncovers teacher educators' perceptions of edTPA and their subsequent actions in response to a state mandate resulting in educative strategies to support their candidates, curriculum change, and lessons learned.